2020
DOI: 10.1590/s2175-97902019000418401
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric micelles containing resveratrol: development, characterization, cytotoxicity on tumor cells and antimicrobial activity

Abstract: Antimicrobial and antitumor activities of resveratrol, a compound found mainly in grapes, have already been demonstrated. However, its low bioavailability is a limiting factor for therapeutic application. Polymeric micelles can be an approach to solve this problem since they can encapsulate hydrophobic substances. We developed and characterized micellar formulations containing resveratrol and evaluated their cytotoxic and antimicrobial effects. The formulations were prepared by the cold dispersion method with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Other beneficial effects of oral RSV administration within the CNS are discussed in detail elsewhere [42,43,48,49]. Improvement of the bioavailability of RSV as a dietary supplement is achieved by opsonization of the RSV molecule with lipophilic particles [51], by its nanoencapsulation within liposomes or micelles, increasing its intestinal absorption [181,182], by modification of the RSV molecular structure (e.g., hydroxylation or metoxylation of its aromatic rings) [183], or by its intrathecal administration, leading to increased penetration through the BBB into the CSF [175].…”
Section: Discussionmentioning
confidence: 99%
“…Other beneficial effects of oral RSV administration within the CNS are discussed in detail elsewhere [42,43,48,49]. Improvement of the bioavailability of RSV as a dietary supplement is achieved by opsonization of the RSV molecule with lipophilic particles [51], by its nanoencapsulation within liposomes or micelles, increasing its intestinal absorption [181,182], by modification of the RSV molecular structure (e.g., hydroxylation or metoxylation of its aromatic rings) [183], or by its intrathecal administration, leading to increased penetration through the BBB into the CSF [175].…”
Section: Discussionmentioning
confidence: 99%
“…Micellar formulations enhance the permeation and uptake of RSV both in vitro and in vivo, specifically in corneal permeation (Li, Zhang, et al, 2020). Micelles containing RSV have improved RSV bioavailability and maintained the antimicrobial and cytotoxic activity of RSV‐containing pluronic F127 (F127)‐micelles against bladder cancer cells (Almeida et al, 2020). Trans‐RSV is a polyphenol with broad therapeutic utility but has poor bioavailability and limited distribution across the blood–brain barrier.…”
Section: Nanotechnology Solutions As a Promising Practical Approach I...mentioning
confidence: 99%
“…The activity of RSV loaded in nanoformulation, aiming its use in blader cancer, was investigated only by Almeida et al (2020 ). The authors showed that polymeric micelles were able to preserve the cytotoxic activity of free resveratrol in RT4 and T24 cells.…”
Section: In Vitro Studies About Resveratrol Effects On Blamentioning
confidence: 99%